Disparities in Inherited Retinal Degenerations. (17th February 2023) - Chorfi, Sarah; Place, Emily M.; Huckfeldt, Rachel M.
ABSTRACT: To review disparities in the field of inherited retinal degenerations to establish foundations for future discussions oriented toward finding possible solutions. A narrative overview of the literature. Despite collective efforts towards democratization of genetic testing and investigation, genetic databases containing primarily European populations are heavily relied upon. Access to specialized care and other resources is also still not available to all. Recognizing and addressing disparities and inequities within the field of inherited retinal degenerations will improve our care of these patients and our knowledge of their conditions.